The intergenerational creative arts project - Sellers, Debra M., 1967- (My University, 2015)
The Intergenerational Creative Arts Project attempted to address these long-standing and in today’s world, even more complex concerns. The goals of the project were to begin to change perception, attitudes, and policy towards marginalized elders and to ensure their inclusion in the community life through the development of a family-based program within the long term care setting. the Intergeneration Creative Arts Project utilized the three modalities of drama therapy, animal assisted therapy, and intergenerational programming to assist elders to become contributing members of the community, to develop meaningful relationships among generations, and to establish the long term care facility as a thriving, community-based organization through outreach to elders’ families and friends. This paper describes the development, implementation, and evaluation of the project.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Sellers, D. M. (2002). The intergenerational creative arts project. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Intergenerational relations; Arts and older people; Nursing homes--Recreational activities; Reports; Reports